Probing the solute-solvent interactions in the binary mixtures of ionic liquids with water and alcohols by conductance, viscosity and IR spectroscopy - Jain, Preeti; Kumar, Anil (Journal of Molecular Liquids, 2017)
The molar conductance and viscosities of the bisulfate ([HSO4](-)) and ethylsulfate ([EtSO4](-))-based imidazolium ionic liquids in various molecular solvents have been measured at 298.15 K as a function of concentration of ionic liquids (1 x 10(-4) to 0.1 mol L-1). It is shown that the anions have considerable effect on the molar conductance and association constant of the [HSO4](-) and [EtSO4](-)-based imidazolium ionic liquids. Higher molar conductance of the [HSO4](-)-based imidazolium ionic liquids in polar protic solvents (water and methanol) is noted as compared to the [EtSO4](-)-based imidazolium ionic liquids, though the [HSO4](-)-based imidazolium ionic liquids possess higher association constant in water than in methanol. The intermolecular interactions in the pure and binary mixture of [HSO4](-) and [EtSO4](-)-based imidazolium ionic liquids have been investigated by IR spectroscopy. The C-2-H stretching vibration frequency of the imidazolium ring reveals the H-bonding between cations and anions of pure ionic liquids and their solutions. The transport properties (limiting molar conductance, transport number, ionic mobility and diffusion coefficient) of cations and anions correlate well with the hydrodynamic radius in their aqueous solutions. The study shows that the energy barrier for charge transfer is minimal as compared to the fluidity of the aqueous solution of the studied ionic liquids obtained from the Arrhenius equation. (C) 2017 Elsevier B.V. All rights reserved.